Design, analysis and optimization of thin walled semi-monocoque wing structures using different structural idealization in the preliminary design phase. Issue 3 (28th August 2014) - DABABNEH, ODEH; KAYRAN, ALTAN
Abstract : Purpose: In modeling an aircraft wing, structural idealizations are often employed in hand calculations to simplify the structural analysis. In real applications of structural design, analysis and optimization, finite element methods are used because of the complexity of the geometry, combined and complex loading conditions. This article gives a a comprehensive study on the effect of using different structural idealizations on the design, analysis and optimization of thin walled semi-monocoque wing structures in the preliminary design phase. Design/methodology/approach: In the design part of the article, wing structures are designed by employing two different structural idealizations that are typically used in the preliminary design phase. In the structural analysis part, finite element analysis of one of the designed wing configurations is performed using six different one and two dimensional finite element pairs which are typically used to model the sub-elements of semi-monocoque wing structures. Finally in the optimization part, wing structure is optimized for minimum weight by using finite element models which have the same six different finite element pairs used in the analysis phase. Findings: Based on the results presented in the article, it is concluded that with the simplified methods, preliminary sizing of the wing configurations can be performed with enough confidence as long as the simplified method based designs are also optimized iteratively, which is what is practiced in the design phase of this study. Originality/value: This research aims at investigating the effect of using different one and two dimensional element pairs on the final analysed and optimized configurations of the wing structure., and Cconclusions are inferred with regard to the sensitivity of the optimized wing configurations with respect to the choice of different element types in the finite element model.